(untitled) (Eurasian Journal of Learning and Academic Teaching, 2022)
There are many studies on euphemisms. The scientific literature has given different descriptions of this phenomenon. The main reason for the multifaceted, changing nature of euphemism is the diversity of its lexical-grammatical form, the presence of emotional colourlessness, methodological neutrality, and features of variability. For a word to work as a euphemism, its interpretation must remain vague in relation to the listener. They interpret it literally or euphemistically. As the scope of euphemism expands, it becomes more synonymous with the original term than a euphemism. The purpose of this article is to identify the most effective and common forms of political euphemisms, as well as the specific features of terminological changes.